Daclatasvir plus asunaprevir for chronic HCV genotype 1b infection. Issue 6 (1st April 2014) - Kumada, Hiromitsu; Suzuki, Yoshiyuki; Ikeda, Kenji; Toyota, Joji; Karino, Yoshiyasu; Chayama, Kazuaki; Kawakami, Yoshiiku; Ido, Akio; Yamamoto, Kazuhide; Takaguchi, Koichi; Izumi, Namiki; Koike, Kazuhiko; et al.
<x xml:space="preserve">Abstract</x> All‐oral combinations of direct‐acting antivirals may improve efficacy and safety outcomes for patients with hepatitis C virus (HCV) infection, particularly those who are poor candidates for current interferon/ribavirin‐based regimens. In this open‐label, phase 3 study, 135 interferon‐ineligible/intolerant and 87 nonresponder patients with chronic HCV genotype 1b infection were enrolled at 24 centers in Japan. Patients received daclatasvir 60 mg once daily plus asunaprevir 100 mg twice daily for 24 weeks. The primary endpoint was sustained virologic response 24 weeks after treatment (SVR24). This study is registered with ClinicalTrials.gov (NCT01497834). SVR24 was achieved by 87.4% of interferon‐ineligible/intolerant patients and 80.5% of nonresponder (null and partial) patients; rates were similar in cirrhosis (90.9%) and noncirrhosis (84.0%) patients, and in patients with IL28B CC (84.5%) or non‐CC (84.8%) genotypes. Fourteen patients in each group (12.6%) discontinued dual therapy, mainly due to adverse events or lack of efficacy. Nine nonresponder patients received additional treatment with peginterferon/ribavirin per protocol‐defined criteria. The rate of serious adverse events was low (5.9%) and varied among patients. The most common adverse events were nasopharyngitis, increased alanine aminotransferase (ALT) and aspartate aminotransferase (AST), headache, diarrhea, and pyrexia. Conclusion: Interferon‐free, ribavirin‐free all‐oral therapy with daclatasvir and asunaprevir for 24 weeks is well tolerated and can achieve a high rate of SVR in patients with HCV genotype 1b who were ineligible, intolerant, or had not responded to prior interferon‐based therapy. (Hepatology 2014;59:2083–2091)